Understanding the Influence of Corporate Social Responsibility on Brand Management: A Qualitative Analysis - Muhammad Rizal; Ngadi Permana; Eri Kusnanto (LPPM STIE Kasih Bangsa, 2024)
This qualitative research aims to investigate Indonesian adolescents' perceptions of online learning amid the COVID-19 pandemic. Employing a phenomenological research model, the study delves into the lived experiences and perspectives of adolescents regarding the transition to online education. A purposive sampling technique was utilized to select participants from diverse socioeconomic backgrounds. Data collection involved in-depth interviews and thematic analysis, allowing for a comprehensive understanding of participants' viewpoints. Findings reveal nuanced insights into adolescents' experiences, challenges, and preferences in online learning environments. The study underscores the importance of addressing technological access, pedagogical approaches, and socio-emotional support to enhance the effectiveness of online education for adolescents in Indonesia.